Flexisecurity as a paradigm of European employment policies: A critical review - Ojeda Avilés, Antonio (2014)
Employment flexibility and employment stability are concepts that, historically, have been found to be opposite to one another within Labor Law. It is in the middle of this context that Flexisecurity is born, being a concept that unifies the two notions with theaim of protecting both sides of the employment relationship: The employer and the employee.The authors undertake a critical review of the concept of flexisecurity based on the definition established by multinational organisms, especially the Community institutions of the European Union. To do so, they take off from the concept of “flexisecurity” and the different opinions it has raised within the Community level, always taking into account the common flexisecurity principles as they have be endeveloped by the European Commission.